A COMPARATIVE RANDOMIZED CLINICAL TRIAL OF NIPRD AM1 AGAINST A CHLOROQUINE AND SULPHADOXINE/PYRIMETHAMINE COMBINATION IN SYMPTOMATIC BUT UNCOMPLICATED MALARIA - Gamaniel, K. (African Journal of Traditional, Complementary and Alternative Medicines, 2009)
NIPRD 92/001/1-1 is a single plant preparation used in Africa to treat malaria and other ailments. The plant occurs widely in continental Africa where the various parts are used. The plant is also used extensively as a food source. The root extracts are usually preferred for the treatment of malaria. We studied the non-clinical efficacy and safety profile of NIPRD AM 1 against P. berghei in mice and found the product to be safe and effective. The results of our phytochemical studies on the plant extract revealed the presence of alkaloids, tannins and saponins and an aqueous extract yield of 3.6% w/w. The product had an LD50 > 2000mg/kg p.o. in rats and mice and did not show any significant toxic activity within the organs or systems in the 28 day sub-acute toxicity study. However, there was a decrease in food consumption and weight loss associated with the product. NIPRD AM 1 also significantly reduced the spontaneous motor activity (SMA) in mice. A comparative randomized clinical trial of NIPRD AM 1 was carried out against symptomatic but uncomplicated Malaria in human volunteers at the two district hospitals located in Gwagwalada and Wuse, both in the Federal Capital Territory, Abuja, Nigeria. NIPRD AM1 was studied against a chloroquine and sulphadoxine/pyrimethamine (Fansidar) combination. The results indicated that NIPRD AM 1 was effective against uncomplicated malaria with its activity superior to that of CQ and SP. The parasite clearance was better than that of chloroquine and there were no threats of serious side effects affecting the organs or tissues. Acknowledgements: WHO TDR provided funding.